Case Study: Role of Media in Policy Making: Special Reference to Afghanistan - Mangal, Farooq Jan (Integrated Journal for Research in Arts and Humanities, 2022)
Mass media (Radio, TV, print…) plays a crucial and vital role in information distribution and thus in the political market and public policy making. Theory predicts that information provided by mass media reflects the media’s incentives to provide news to different types of groups in society, and affects these groups’ influence in policy-making. The study emphasize on the role of mass media in political markets and its effect on public policy-making. It attempts to develop a theoretical relationship between mass media and public policy. The empirical studies have tried to assess the effect of media on policy outcomes. Analysing various cases in Afghanistan, media influences policy makers and higher authorities to act in accordance of the suggestion and recommendations of media workers and institutions. In recent decades, policy makers have considered on media’s soft and proper demands based on their suggestions and recommendations, even many articles in Afghanistan’s constitution would be amended. According to our findings, ‘Access to Information Law’, passed by president Ashraf Ghani, was a combine demand of policy makers, lawyers and media workers, who believed that legal information except the information that can harm national security should be accessible by locals and media workers through law. Similarly, Afghan Journalist safety committee developed a comprehensive policy against women Sexual harassment that will be discussed in the paper as a ‘Case Study’. Hence, the policy has been accepted by Government of Afghanistan and is implemented since then.